Functional effects of cortical auditory evoked potentials and hearing ADIS on speech perception in sensorineural hearing loss individuals / Mohammed Gamal Nasser Al-Zidi - Mohammed Gamal, Nasser Al-Zidi (2018)
Cortical Auditory Evoked Potentials (CAEPs) represent summation of neural activity in the auditory pathways in reaction to sounds. They provide an objective measure of the brain’s response to sound. For this reason, CAEPs are an ideal tool for scientists and audiologists for investigating auditory function in people both, normal and with hearing loss. The main objective of this study is to determine which CAEP components among the P1, N1, P2, N2, or P3 are most beneficial in assessing the speech detection and discrimination abilities of adults Sensorineural Hearing Loss (SNHL) population. This study also intends to investigate whether changes in the amplitudes and latencies of these CAEP components occurring with SNHL and hearing aids reflect various stages of auditory processing. CAEPs were recorded from two groups of participants. A control group that comprising of 12 right-handed Malay adults having normal hearing and a second group that consists of 10 right-handed Malay adults with sensorineural hearing loss who were recruited from the local community in the department of Otorhinolaryngology (ENT), UMMC hospital, Kuala Lumpur. The results showed that P2 and P3 components had the most benefits from the use of hearing aids in the SNHL subjects and could be used in both clinical and research applications as a predictor and objective indicator of hearing aids performance in speech perception. The study also showed that the brain processes both stimuli in a different pattern for both normal and aided SNHL subjects. These findings suggest that the aided SNHL subject, despite the benefits they get from the hearing aids, find it difficult to detect and discriminate the acoustic differences between the two speech stimuli. The present study could provide more diagnostic information for clinicians and could also offer better speech perception benefits for hearing-impaired individuals from their personal hearing aids.